Cenozoic history of Antarctic benthic diatoms - Whitehead, JM (2005)
Antarctic Cenozoic climate changes have influenced the development of the Southern Ocean benthic diatom flora. When Antarctica and South America separated in the late Eocene (∼37 Ma), giving rise to the proto-Antarctic Circumpolar Current (ACC), the environment gradually changed from temperate alpine glacial to subpolar with ice sheet development. By the early Oligocene (∼30 Ma), at least thirteen new benthic diatom genera had appeared in the Antarctic. Many of the genera probably migrated from lower latitudes (e.g. New Zealand) prior to the ACC becoming fully established (23 ± 2.5 Ma), which increased the physical separation of Antarctica. Further migration may have occurred during later periods of climate warming, but the Cenozoic was generally a time of progressive climate cooling, and increased glaciation that may have caused diatom extinctions. Some genera became extinct during the late Pliocene and Pleistocene, for example, when glaciers covered much of the Antarctic continental shelf. Many of the benthic diatom genera now extinct in Antarctica still occur in ice-free environments at lower latitudes. Most extant benthic Antarctic diatom taxa are eurytopic and probably survived Cenozoic glaciations by either inhabiting sea-ice or becoming planktic, as sea-floor habitats were restricted. © AAP.